Long-Range “Talking” of Vector Solitons and their Synchronization in Fabry-Pérot Resonators - Hill, Lewis; Hirmer, Eva Maria; Campbell, Graeme; Bi, Toby; Ghosh, Alekhya; Oppo, Gian Luca; Del'Haye, Pascal (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
A suitable Fabry-Pérot (FP) cavity, Fig. 1(a), filled with a Kerr medium with anomalous dispersion can support temporal cavity solitons (TCS) [1]. Kerr FP cavities have also been shown to exhibit a spontaneous symmetry breaking (SSB) [2] between the powers of orthogonally polarized light components [3]. Just as these phenomena have been combined in Kerr ring resonators [4,5], we investigate the SSB of TCS in Kerr linear resonators. Figure 1(b) shows this SSB of TCS, where, in the vector soliton pair, one notes that one polarization is dominant over the other, thus realizing a linear cavity source of symmetry broken vectorial Kerr frequency combs, Fig. 1(c). We discuss here a number of further, fascinating and useful, results not possible in the previous Kerr ring studies.
CRIS-Team Scopus Importer:2024-12-16